Dysregulated renal tubular handling of filtered glucose in patients with type 2 diabetes mellitus: a descriptive study - Asim Zulfiqar; Saira Jahan; Muhammad Nadim Akbar Khan; Shamaila Burney; Muhammad Farooq; Kiran Fatima (Journal of the Pakistan Medical Association)
Objective: To determine the frequency of suspected dysregulated renal tubular handling of filtered glucose, and its association with blood glucose levels in type 2 diabetes mellitus.